Basic Elements of General Gymnastics Routines that Contribute to the Multiple Development of Motor and Social Skills in Children of 4-8 Years Old - Pollatou, Ελιζάνα (Inquiries in Physical Education and Sport, 2003)
The purpose of the present study was to refer basic elements of general gymnastics routines and analyze the multiple effect of systematic involvement with them in the development of gross and fine motor skills and social skills also, in boys and girls from four to eight years old. More specifically, there referred skills that contribute to the cultivation of kinesthesis, space awareness, and sense of rhythm while it is improved the performance in apparatus manipulation either they are pure gymnastic or usable objects or original products of creative fantasy. The musical accompaniment enhances the reaction ability in multiple sound stimuli, while exercising in collaboration with other members of the team develops relationships of respect and acceptance of each one’s individual differences. That way it is attained an artful development of personality of children while it is establishing the lifetime involvement in physical activity.